2020
DOI: 10.5114/fmpcr.2020.95328
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pelvic floor muscle exercises on sexual function in women with multiple sclerosis: a pre – post intervention clinical trial

Abstract: Background. Sexual dysfunction (SD) is a common symptom in patients with multiple sclerosis (MS). In women with MS, there are no specific pharmacological or non-pharmacological therapies which have been proven effective for SD. Objectives. The main objective of this study was to evaluate the effect of pelvic floor muscle exercises on improving sexual function in women with MS. Material and methods. This study was a pre-/post-intervention clinical trial conducted on 45 MS women who had been referred to the MS C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…One study specifically reported overactive bladder as an independent factor of SD in women with MS [ 43 ]. For those women suffering from sphincter symptoms, therapeutic interventions have shown an improvement in SD after non-blinded, single-arm trials [ 63 65 ]. The potential negative effect of CNS depressants on SD in our population was observed but did not reach statistical significance after correcting for multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…One study specifically reported overactive bladder as an independent factor of SD in women with MS [ 43 ]. For those women suffering from sphincter symptoms, therapeutic interventions have shown an improvement in SD after non-blinded, single-arm trials [ 63 65 ]. The potential negative effect of CNS depressants on SD in our population was observed but did not reach statistical significance after correcting for multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%